Introducing Cultural Heritage through Malay Tanjak Making Practices at Sentul Guidance Studio, Kuala Lumpur, Malaysia - Muhammad Saleh; Ahmad Zaki; Enda Lovita Pandiangan; Nadia Aulina Matondang; Jannah Jannah (Sultan Publisher, 2025)
Malay tanjak making training at Sentul Guidance Studio Kuala Lumpur aims to preserve Malay cultural heritage and increase the cultural literacy of early childhood students living abroad, especially Indonesian children in Malaysia. This activity is also part of the International Community Service Program (KKN) of Jam'iyah Mahmudiyah Langkat Institute students. The method used in this activity is a qualitative descriptive one that uses direct observation.The implementation of the activity involved two main stages: socialization and introduction of the Malay tanjak, as well as the direct practice of making tanjak. The results of the activity showed that this training succeeded in increasing the participants’ understanding of Malay culture as well as their skills in making tanjak. In addition to providing cultural education, the activity can build a sense of pride in ancestral cultural heritage. Participants showed high enthusiasm in following all stages of the training, and some even took the initiative to develop these skills further. Thus, this activity made a positive contribution to the preservation of and strengthening Malay cultural identity among the overseas young generation.